Preoperative predictors of restoration in quality of life after surgery for lung cancer. Issue 6 (28th January 2021) - Ichimura, Hideo; Kobayashi, Keisuke; Gosho, Masahiko; Nakaoka, Kojiro; Yanagihara, Takahiro; Ueda, Sho; Saeki, Yusuke; Maki, Naoki; Kobayashi, Naohiro; Kikuchi, Shinji; Suzuki, Hisashi; Goto, Yukinobu; et al.
Abstract: Background: The preoperative predictors of quality of life (QOL) in patients who undergo lung resection for lung cancer are poorly known. Here, we investigated these predictors in such patients using two QOL measures. Methods: In this single‐institutional prospective cohort study, we administered the EQ‐5D‐5 levels (EQ‐5D‐5L) from January 2015, and the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire with 30 items from April 2015 to April 2018 preoperatively (Pre) and at one month postoperatively (M1), and one year postoperatively (Y1). General health status was measured by the EQ‐5D visual analogue scale (VAS) and EORTC global health status/QOL (GHS) scores. Multivariable linear regression analyses were used to explore the preoperative predictors of QOL at Y1. Results: A total of 223 patients were included in the study. The EQ‐5D VAS and EORTC GHS scores, at Pre, M1, and Y1, were 80 ± 15, 77 ± 15, and 84 ± 11; and 74 ± 19, 65 ± 20, and 78 ± 17, respectively. In the multivariable analyses, the albumin level, preoperative VAS score, and preoperative pain/discomfort and anxiety/depression were identified as predictors by the EQ‐5D VAS score. The preoperative EORTC GHS score, absence of diabetes mellitus, preoperative cognitive function score, and preoperative symptom score of pain were identified as predictors by the EORTC GHS score. Conclusions: The EQ‐5D VAS and EORTC GHS scores traced similar trajectories of QOL. In both QOL measures, preoperative pain was found as a common predictor. These predictors may help improve patient/survivor care in the future. Abstract : We investigated the preoperative predictors of QOL in surgical patients with lung cancer. General health status/QOL was measured by EQ‐5D VAS and EORTC GHS scores. Multivariable linear regression analyses were used. Although each QOL measure detected some preoperative predictors, preoperative pain was a common predictor in both, one year after surgery. Predictors detected in this study were possible targets for patient/survivor care.